Quantification of left coronary bifurcation angles and plaques by coronary computed tomography angiography for prediction of significant coronary stenosis: A preliminary study with dual-source CT. - Yue Cui; Wenjuan Zeng; Jie Yu; Jing Lu; Yuannan Hu; Nan Diao; Bo Liang; Ping Han; Heshui Shi (PLoS ONE, 2017)
PURPOSE:To evaluate the diagnostic performance of left coronary bifurcation angles and plaque characteristics for prediction of coronary stenosis by dual-source CT. METHODS:106 patients suspected of coronary artery disease undergoing both coronary computed tomography angiography (CCTA) and invasive coronary angiography (CAG) within three months were included. Left coronary bifurcation angles including the angles between the left anterior descending artery and left circumflex artery (LAD-LCx), left main coronary artery and left anterior descending artery (LM-LAD), left main coronary artery and left circumflex artery (LM-LCx) were measured on CT images. CCTA plaque parameters were calculated by plaque analysis software. Coronary stenosis ≥ 50% by CAG was defined as significant. RESULTS:106 patients with 318 left coronary bifurcation angles and 126 vessels were analyzed. The bifurcation angle of LAD-LCx was significantly larger in left coronary stenosis ≥ 50% than stenosis < 50%, and significantly wider in the non-calcified plaque group than calcified. Multivariable analyses showed the bifurcation angle of LAD-LCx was an independent predictor for significant left coronary stenosis (OR = 1.423, P = 0.002). In ROC curve analysis, LAD-LCx predicted significant left coronary stenosis with a sensitivity of 66.7%, specificity of 78.4%, positive predictive value of 85.2% and negative predictive value of 55.8%. The lipid plaque volume improved the diagnostic performance of CCTA diameter stenosis (AUC: 0.854 vs. 0.900, P = 0.045) in significant coronary stenosis. CONCLUSIONS:The bifurcation angle of LAD-LCx could predict significant left coronary stenosis. Wider LAD-LCx is related to non-calcified lesions. Lipid plaque volume could improve the diagnostic performance of CCTA for coronary stenosis prediction.